Питання розробки систем бездротового зв'язку - Гришков, С. В. (ХНУРЕ, 2022)
Designing security, communication and alarm systems in residential, or industrial, office buildings, the question of building local networks arises and, above all, the developers face a dilemma – wired or wireless network. For economic reasons, the decision is often in favor of wired networks. But sometimes you need to abandon simple solutions in favor of innovations that provide more scalability, deployment speed, and network configuration.